Seismicity and geodynamics of western Peloponnese and central Ionian Islands: Insights from a local seismic deployment - A. Haddad; A. Ganas; Kassaras, I.; M. Lupi (Tectonophysics, 2020)
The tectonic setting of western Peloponnese and central Ionian Islands, Greece, is characterized by the subduction of the oceanic African plate beneath the Aegean micro-plate. The transition from subduction to continental collision in northwestern Greece is accommodated by the right-lateral Cephalonia transform fault. In this work, we exploit the recordings of a temporary seismic network composed of 15 stations operating from July 2016 until May 2017 to investigate the complex deformation of this region. Our local network fills in a major observational gap in one of the most tectonically active regions of the Hellenic arc. We detected and located more than 1200 local earthquakes and constrained five 1D optimum local velocity models. The relocated seismicity (including the aftershock sequence that followed the October 2018 Mw 6.7 earthquake offshore Zakynthos) and associated focal mechanisms constrained for the major earthquakes point out a complex crustal deformation. We propose a clockwise rotation of the Ionian Akarnania Block accommodated by major marginal strike-slip fault zones that appear segmented along their strike. Additionally, left-lateral motion is observed on the Kyllini-Cephalonia fault along a north-west direction. Finally, the seismicity recorded in north Cephalonia (offshore Myrtos and Fiskardo) suggests that the Cephalonia transform fault is a large deformation zone where secondary WNW-striking sinistral strike-slip faults occur.
Keywords: Cephalonia Transform Fault; Earthquake relocation; Seismo-tectonics; Western Greece